Path Analysis Model to Assess the Effects of Anthropometry and Power on the Vertical Jump Performance of Youth Volleyball Athletes - Putra, Martinez Edison; Kurniawan, Faidillah; Fauziah, Ella; Ningrum, Novi Resmi (JUMORA: Jurnal Moderasi Olahraga, 2025)
Background. length of lower leg, body mass index (BMI), and power affects the vertical jump performance of volleyball. The direct and indirect relationships of such variables have not been thoroughly explored. Purpose. Evaluate how power functions as a mediator and how lower leg length and BMI impact vertical jump performance. Method. This study has a quantitative design and uses methods path analysis. The purposive sampling method was used to select 24 volleyball athletes, each with an average age of 18.46 years. Anthropometric, BMI, power, and vertical jump performance data were directly collected and tested using a path analysis model using SPSS and AMOS software version 26. Results. Lower leg length has a negative direct impact on jump performance (-0.308; p< 0.05), but has a positive impact on power (0.481; p< 0.05). BMI has a negative direct impact on vertical jump performance (-1,032; p <0.05), but has a positive impact on power (0.713; p< 0.05). Power mediation is responsible for 94.5% of vertical jump performance variance, indicating that this element is crucial in the relationship between leg length and BMI with vertical jump. conclusion. Although lower leg length and BMI have a negative effect on vertical jump performance, power is an important mediator in the relationship between lower leg length and BMI to vertical jump. Exercises that focus on developing effective power to improve jump performance